2005
DOI: 10.1007/s00442-005-0228-8
|View full text |Cite
|
Sign up to set email alerts
|

Population trends associated with skin peptide defenses against chytridiomycosis in Australian frogs

Abstract: Many species of amphibians in the wet tropics of Australia have experienced population declines linked with the emergence of a skin-invasive chytrid fungus, Batrachochytrium dendrobatidis. An innate defense, antimicrobial peptides produced by granular glands in the skin, may protect some species from disease. Here we present evidence that supports this hypothesis. We tested ten synthesized peptides produced by Australian species, and natural peptide mixtures from five Queensland rainforest species. Natural mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 55 publications
(71 reference statements)
4
131
1
5
Order By: Relevance
“…For example, species with potentially weak predicted defenses may be targeted for captive husbandry. However, the link between in vitro peptide effectiveness and protection in the wild is tentative (Woodhams et al, 2006).…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, species with potentially weak predicted defenses may be targeted for captive husbandry. However, the link between in vitro peptide effectiveness and protection in the wild is tentative (Woodhams et al, 2006).…”
Section: Discussion Predicting Immunologic Resistance To Chytridiomycmentioning
confidence: 99%
“…Chytridiomycosis is an emerging infectious disease of amphibians caused by Batrachochytrium dendrobatidis that affects some species more than others within an assemblage (Berger et al, 1998;Lips et al, 2003b;Retallick et al, 2004;Woodhams and Alford, 2005). For example, chytridiomycosis-associated population declines in Queensland, Australia, may have contributed to the extirpation of some species from high elevations, whereas other species persisted in the same habitat (Richards et al, 1993;Berger et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Woodhams et al (2005), using collection procedures similar to those in this study, examined five species of Australian frogs and found total peptide levels ranging from 10.5 to 29.6 mg/gram body weight. This is in contrast to the 325-400 mg/gram body weight collected from tiger salamanders (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…The relative amounts of active peptides produced by each acclimation treatment were compared using MIC equivalent measures per gram of body weight and per cm 2 of surface area. MIC equivalents are defined as the total amount of peptides recovered (mg) per gram weight or per cm 2 surface area divided by the experimentally determined MIC (mg/ml) for each treatment (Woodhams et al, 2005). Surface area of the salamanders in cm 2 was calculated using the following allometric equation: surface area58.42 3 (weight in grams) 0.694 (Whitford and Hutchinson, 1967).…”
Section: Batrachochytrium Assaysmentioning
confidence: 99%